Implementing a singing-based intervention for postpartum depression in Denmark and Romania: a brief research report - Katey Warran; Calum Smith; Calum Smith; Hanna Ugron; Oana Blaga; Nicolai Lund Ladegaard; Nicolai Lund Ladegaard; Louise Frøkjær Carstens; Lucy Nicholls; Alexandra Burton; Rarita Zbranca; Mikkel Ottow; et al. (Frontiers in Medicine, 2023)
BackgroundThere is a burgeoning evidence-base that demonstrates the positive impact of the arts on our health, wellbeing, and health behaviors. However, very few studies have focused on how to optimize the implementation of these activities for different sociocultural contexts. Due to the increasing interest in scaling effective arts interventions as part of public health strategies, and in line with global goals of achieving health equity, this is an essential focus.AimUsing the case study of a singing for post-partum depression (PPD) intervention with empirically-demonstrated clinical effects, this brief research report explores implementation of an arts and health intervention that has been successful in the United Kingdom (“Music and Motherhood”) for the new contexts of Silkeborg (Denmark) and Cluj-Napoca (Romania).MethodsData was collected from participants at all levels of the implementation structure including at local and management levels. The study draws on qualitative implementation data to explore participant experiences, including one-to-one interviews, written testimonies, meeting minutes, ethnographic researcher reflections and focus groups, including data from 46 participants in total.Results and conclusionWe explore implementation and adaptation across five key themes: (1) acceptability and feasibility; (2) practical and structural barriers and enablers; (3) adoption and sustainability; (4) broader contextual factors affecting implementation and sustainability; and (5) project structure and processes. Taken together, the themes demonstrate that arts interventions need to be adapted in culturally sensitive ways by stakeholders who have local knowledge of their environments. This research serves as an informative foundation for use by other researchers that aim to expand the reach and impact of arts-based interventions.